Orientalistische Literaturzeitung : Zeitschrift für die Wissenschaft vom ganzen Orient und seinen Beziehungen zu den angrenzenden Kulturkreisen (De Gruyter (A), 1898)
The Orientalistische Literaturzeitung is the oldest international review journal covering the field of Oriental studies. Founded in 1898, in keeping with the development of the field, it has widened its scope and covers all time periods.